“MY MARXIST FEMINIST DIALECTIC BRINGS ALL THE BOYS TO THE YARD”: WHAT MARXIST FEMINIST THEORY CAN TELL US ABOUT CONSUMER LABOUR IN DIGITAL MEDIA - Jarrett, Kylie (AoIR Selected Papers of Internet Research, 2014)
The activities of consumers in digital media environments have increasingly been conceptualised as labour. Consumers are understood to provide unpaid labour by contributing content to websites in the form of game play, videos, memes, status updates and the affective investment that renders commercial digital media pleasurable and meaningful. Consumer activity also forms the data that is captured by the economic systems of such sites, with clickstream data and taste information being onsold to advertisers and marketing companies. Beginning with the important work of Tiziana Terranova (2000) and through the rigorous theorisations of Christian Fuchs (2008: 2009; see also Cohen 2008: Scholz (ed.) 2013; Kücklich 2005), it has also become common to view this labour as exploited. However, this argument has not gone unchallenged. Theorists such as Mark Andrejevic (2009), David Hesmondhalgh (2010) and John Banks and Sal Humphreys (2008) question the designation of such exchanges as exploitative. The conditions and experiences associated with alienated industrialised labour do not directly correspond with the experiences of consumers in digital media contexts. The voluntary nature of these exchanges, particularly when compared to (compulsory) waged labour, raises questions about this application of Marxist thought. I will argue in this theoretical paper that Marxist Feminist theory, particularly that used to explain the economic role of domestic labour, offers a way out of this impasse.